PERTUMBUHAN BIBIT MALAPARI DARI PROVENAN UJUNG KULON PADA UMUR 5 BULAN DI PERSEMAIAN - Tri Maria Hasnah; Eritrina Windyarini; Budi Leksono; Hamdan Adma Adinugraha; Lukman Hakim (Jurnal Pemuliaan Tanaman Hutan, 2021)
Malapari (Pongamia pinnata) is one of tree species belonging to Family of Leguminosae. Malapari seed oil were known as potential source for biofuel. The previous study showed that Provenance from Taman Nasional Ujung Kulon Banten had highest oil content among provenances in Java. Seed exploration was carried out to determine variations among families on oil content and growth performance. This study was conducted to determine the variation among families on growth performance at nursery level. The seedlings were used as planting stocks for Progeny Test establishment. This study was arranged in randomized completely block design with 50 families, 10 seedlings per plot and repeated in 4 blocks resulting the total number of observation units were 2000 seedlings. Seedling survival rate, growth performance (height, diameter, leave number), and sturdiness ratio was measured monthly up to 5 months after sowing. Analyses of variance was used to find out differences among families. Correlation among characters/parameters was analyzed by Pearson Correlation Analyses. The results showed that variations among families were found on seedling growth performance. The seedling survival rate at the age of 5 months was 84.60% (26,70-100%) with an average growth of 47.10 cm (31,2-59,7 cm) in height, 5.49 mm (4,7-6,5 mm) in diameter, 8.56 for seedlings sturdiness and 15.4 (10,9-18,8) for leave number.